2018
DOI: 10.1016/j.physio.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Does physical activity change following hip and knee replacement? Matched case-control study evaluating Physical Activity Scale for the Elderly data from the Osteoarthritis Initiative

Abstract: Objectives: To determine whether physical activity measured using the Physical Activity Scale for the Elderly (PASE), changes during the initial 24 months post-total hip (THR) or knee replacement (TKR), and how this compares to a matched non-arthroplasty cohort.Design: Case-controlled study analysis of a prospectively collected dataset.Setting: USA community-based.Participants: 116 people post-THR, 105 people post-TKR compared to 663 people who had not undergone THR or TKR, or had hip or knee osteoarthritis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
(3 reference statements)
1
28
0
Order By: Relevance
“…A study by Losina et al demonstrated that financial incentives combined with telephone health coaching and a Fitbit led to a clinically meaningful increase in steps/day within the first 6 months after TKR . Furthermore, our finding that PA did not change from 6 to 12 months after surgery is consistent with the literature . In a meta‐analysis, Hammett et al observed no change in PA at 6 months after TKR, with only a small change in PA at 12 months .…”
Section: Discussionsupporting
confidence: 91%
“…A study by Losina et al demonstrated that financial incentives combined with telephone health coaching and a Fitbit led to a clinically meaningful increase in steps/day within the first 6 months after TKR . Furthermore, our finding that PA did not change from 6 to 12 months after surgery is consistent with the literature . In a meta‐analysis, Hammett et al observed no change in PA at 6 months after TKR, with only a small change in PA at 12 months .…”
Section: Discussionsupporting
confidence: 91%
“…Due to an inability to collect both objectively measured and patient‐reported volume data from a national cohort, we did not seek to determine the proportion of respondents achieving the recommended levels of weekly physical activity pre‐ and postsurgery. Based on previous studies demonstrating that very few patients achieve the levels recommended , we feel that many are possibly not achieving the recommended levels and, thus, future behavior change interventions will need to focus on both type and quantity of activity, not just participation, if the health of arthroplasty recipients is to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective longitudinal studies , cross‐sectional studies , and several systematic reviews have attempted to quantify or infer changes in activity volume (frequency, intensity, duration) after TKA or THA. Currently, due to limitations in measuring physical activity, differing study designs, and inadequate control of potentially confounding patient covariates, to what extent physical activity increases postsurgery, if at all, is unclear .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations